Sorsogon Center for Culture and Tourism - Faune, Mark Anthony R. (College of Architecture, University of the Philippines Diliman, 2019)
Cultural facilities hold great importance in the fabric of Filipino culture. Spaces wherein people may showcase and express their own unique traditions have become more sought after in an age of rapid growth and progress. And as the country moves forward, local traditions and cultures must also follow suit to ensure survival and development. The motivation for this thesis is an attempt to answer the need for a catalyst in the economic and cultural landscape of Sorsogon through architecture and design, with a view on tourism as a major component in progress. Specifically, this project focuses on the creation of a cultural facility in Sorsogon City that would serve as starting point for an economic and cultural resurgence. The 'Sorsogon Center for Culture and Tourism' utilizes cultural concepts from local traditions and aims to respond to the changing social and economic progress of Sorsogon City.